Spatial and Temporal Protein Modules Signatures Associated with Alzheimer Disease in 3xTg-AD Mice Are Restored by Early Ubiquinol Supplementation - Emilio Llanos-González; Francisco J. Sancho-Bielsa; Javier Frontiñán-Rubio; Yoana Rabanal-Ruíz; Sonia García-Carpintero; Eduardo Chicano; Isabel Úbeda-Banon; Alicia Flores-Cuadrado; Lydia Giménez-Llort; Francisco Javier Alcaín; Juan Ramón Peinado; Mario Durán-Prado (MDPI AG, 2023)
Despite its robust proteopathic nature, the spatiotemporal signature of disrupted protein modules in sporadic Alzheimer's disease (AD) brains remains poorly understood. This considered oxidative stress contributes to AD progression and early intervention with coenzyme Q10 or its reduced form, ubiquinol, delays the progression of the disease. Using MALDI-MSI and functional bioinformatic analysis, we have developed a protocol to express how deregulated protein modules arise from hippocampus and cortex in the AD mice model 3xTG-AD in an age-dependent manner. This strategy allowed us to identify which modules can be efficiently restored to a non-pathological condition by early intervention with ubiquinol. Indeed, an early deregulation of proteostasis-related protein modules, oxidative stress and metabolism has been observed in the hippocampus of 6-month mice (early AD) and the mirrored in cortical regions of 12-month mice (middle/late AD). This observation has been validated by IHC using mouse and human brain sections, suggesting that these protein modules are also affected in humans. The emergence of disrupted protein modules with AD signature can be prevented by early dietary intervention with ubiquinol in the 3xTG-AD mice model.